2005
DOI: 10.1136/bjsm.2005.017806
|View full text |Cite
|
Sign up to set email alerts
|

Effects of inhaled bronchodilators and corticosteroids on exercise induced arterial hypoxaemia in trained male athletes

Abstract: Objectives: To determine the effect of prophylactic treatment with an inhaled bronchodilator and antiinflammatory on arterial saturation (SaO 2 ) in trained non-asthmatic male athletes with exercise induced arterial hypoxaemia (EIAH). Methods: Nine male athletes (mean (SD) age 26.3 (6.7) years, height 182.6 (7.9) cm, weight 79.3 (10.5) kg, VO 2 MAX 62.3 (6.3) ml/kg/min, SaO 2 MIN 92.5 (1.1)%) with no history of asthma were tested in two experimental conditions. A combination of a therapeutic dose of salbutamol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…If the onset of EIAH is mediated by the presence of an inflammatory response and a sub‐clinical, transient pulmonary edema, then individuals lacking abnormally high Q̇ C ’s––and subsequently lacking abnormally high PAP’s––would not be afflicted in the same manner as those who do. This inference garners additional support from the higher arterial oxyhemoglobin saturation values observed in Wetter (Wetter et al, 2002 ) and Hodges (Hodges et al, 2005 ) studies, which were approximately 92% S a O 2 at max exercise in the placebo condition. This is in comparison to the present subjects’ desaturation in the placebo condition to 90% S a O 2 at max, with two individuals reaching nearly 85% S a O 2 .…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…If the onset of EIAH is mediated by the presence of an inflammatory response and a sub‐clinical, transient pulmonary edema, then individuals lacking abnormally high Q̇ C ’s––and subsequently lacking abnormally high PAP’s––would not be afflicted in the same manner as those who do. This inference garners additional support from the higher arterial oxyhemoglobin saturation values observed in Wetter (Wetter et al, 2002 ) and Hodges (Hodges et al, 2005 ) studies, which were approximately 92% S a O 2 at max exercise in the placebo condition. This is in comparison to the present subjects’ desaturation in the placebo condition to 90% S a O 2 at max, with two individuals reaching nearly 85% S a O 2 .…”
Section: Discussionmentioning
confidence: 68%
“…They concluded that “airway inflammation is of insufficient magnitude to cause impairments in gas exchange” as the administered drugs did not alleviate EIAH, nor were increased inflammatory markers observed in post‐exercise sputum (Wetter et al, 2002 ). Additionally, Hodges et al ( 2005 ) found that dosing twice daily over 7 days with a cocktail of 400 µg of salbutamol (selective short acting β 2 ‐adrenergic antagonist bronchodilator) and 500 µg of fluticasone (an anti‐inflammatory corticosteroid) did not significantly affect S a O 2 compared to placebo in nine male cyclists. However, male subjects in the Wetter (Wetter et al, 2002 ) and Hodges (Hodges et al, 2005 ) studies had average V̇O 2max values of <62 ml·kg −1 ·min −1 , whereas our subjects had an average V̇O 2max of nearly 75 ml·kg −1 ·min −1 , with no subjects below 70 ml·kg −1 ·min −1 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…107 According to the IOC Consensus Statement on Asthma in Elite Athletes (January 2008), inhaled corticosteroids are considered as the most effective drugs for long term control of asthma and prevention of EIB. 108 , 109 …”
Section: Pharmacologic Treatmentmentioning
confidence: 99%